A Strategic Choice Theory Taxonomy of Retailers' Strategic Orientations. Issue 2 (2nd April 2016) - Tokman, Mert; Richey, R. Glenn; Deitz, George D.
Abstract : Grounded in strategic choice theory and employing a latent class analysis model of 371 retailers, this study provides a classification of retailer strategic orientations so that the retailers' choice of cooperation levels and ultimately their growth performance can be assessed by their suppliers. The results suggest three major classes of retailers based on their strategic orientations: premium, hybrid, and emergent classes. The outcome of this study guides the supplier partners of retailers in developing and maintaining various levels of cooperative relationships based on uniqueresource needs and expectations of each retailer strategic group.